Der griechisch-orientalische Religionsfonds der Bukowina 1783-1949 Kontinuitäten und Brüche einer prägenden Institution des Josephinismus - Scharr, Kurt (2020)
A comprehensive secularisation process in the course of the Josephinian reforms led to a complete restructuring of church assets. As early as 1783 a Greek-Oriental Religious Fund attributed to the Bukovina was established. Its growing economic and political role made this institution a major factor in the development of the region. It kept this important position until its eventual dissolution in the course of socialist restructuring of Romania in 1949.